ANALISIS DAN STRATEGI PEMANFAATAN KOLEKSI EBOOK PADA PERPUSTAKAAN PERGURUAN TINGGI X: . - Sihite, Desni Sri Hastuti (Perpustakaan Nasional RI, 2024)
This study aims to analyze the utilization of ebook collections as an information resource at University X Library and the challenges faced during the period from 2019 to 2023. The research was conducted using a qualitative approach with a case study method at Library X. The analysis focused on the level of access to ebooks, assessed from several aspects which is: (1) total accesses, (2) chapter downloads, (3) full downloads, (4) online views, (5) print requests, (6) email requests, (7) save requests, (8) turnaways, and (9) abstract requests, for the overall ebook collection available at Library of University X. Data collection was carried out through document analysis, observations, and interviews with librarians. The results showed that the utilization of the ebook collection is still relatively low, which is influenced by several factors namely accessibility, concurrent usage level, and also limited information access of ebook. Therefore, to enhance utilization of the ebook collection in the future, there is a need for the development of more effective and efficient strategies to improve ebook utilization at libraries. This includes reviewing aspects such as accessibility, the content or titles relevant to the needs of the civitas academica, the infrastructure used for access or ease of access, as well as policies regarding access restrictions the collection, in order to ensure that the ebook collection can optimize the role to supporting the implementation of the Tri Dharma of Higher Education.